Knowledge, Attitude and Practice of Evidence-Based Nursing Practice and Barriers - Dwi Novrianda; Hermalinda Herman (Faculty of Nursing Universitas Padjadjaran, 2019)
Professional nurses, one of the human resources in the health sector, are obliged to carry out the nursing process, especially nursing, based on scientific evidence. This study aimed to describe the knowledge, attitudes, and practice of evidence-based practice and its barriers to the hospital. Quantitative research with a descriptive approach was conducted at Dr. M. Djamil Hospital, Padang. A consecutive sampling technique was utilized, with 139 selected nurse practitioners, and only 90 nurses filled in the questionnaires. The instruments used were Evidence-Based Practice Profiles (EBP2) and the BARRIERS Scale. Characteristics of respondents were 70.0% diploma education; mean age was 36.7 (SD=7.95) years and 13.35 (SD=8.37) years of working time. The mean attitude towards EBP was higher than the mean of EBP knowledge/understanding, confidence, understanding of research terms, and practice towards EBP (3.32; 2.93; 2.72; 2.53; 1.95). Therefore, there is a definite need for improving knowledge, comprehending EBP, and research terminology to overcome the obstacles of EBP implementation in the nursing service practice.